Ultrasound Findings in Adult Patients with Chronic Shoulder Pain Having No History of Trauma - Imtiaz, Madiha; Hassan, Khawaja Muhammad Baqir; Sarwar, Shakil; Mushtaq, Ahmed; Talat Yasmeen; Sumera Tabassum (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To evaluate the frequency of non-traumatic chronic shoulder pain sonographically in the local population. METHODOLOGY: This cross-sectional study was conducted at the Department of Radiology, Combined Military Hospital Malir, from March to October 2020. A history of shoulder pain of more than one-month duration was included. Patients with a History of shoulder dislocation, neurological, renal, hepatic and cardiac diseases were excluded. The sample size was 196. A non-probability consecutive sampling technique was employed. SPSS version 23 was used for statistical analysis. RESULTS: 196 patients (69.9% males and 30.1% females) with non-traumatic shoulder pain (56.4 % right side and 43.4% left) were scanned. The mean age was 42.80±11.20 years. Out of 196, 118(60.2%) were having complaints in dominant limbs (right 51.0% and left 9.2%); 78(39.8%) were having pain in non-dominant limbs (right 6.6% and left 33.2%). Significant findings were supraspinatus partial tear (46.9%), sub-acromial sub-deltoid bursitis(8.2%), and biceps tenosynovitis(6.1%), adhesive capsulitis, a complete tear of supraspinatus tendon, impingement syndrome, joint effusion, subscapularis tendon tear and tenosynovitis. 44(22.4%) patients had two pathologies, and 31 (15.8%) patients had three pathologies, respectively. Significant co-existent findings were biceps tenosynovitis (13.8%), Impingement syndrome (9.2%), bursitis (8.2%) and joint effusion (7.1%). Age and number of pathological were moderately positively correlated, r (194) = 0.46, p < 0.01 and keeping CI = 95%. CONCLUSION: Partial tears of the supraspinatus tendon were the most common pathology in non-traumatic shoulder myalgia, diagnosed on ultrasound, followed by sub-acromial sub-deltoid bursitis and biceps tenosynovitis, having moderate linear relation with age.